2009
DOI: 10.1038/bmt.2009.107
|View full text |Cite|
|
Sign up to set email alerts
|

1p21 deletions are strongly associated with 1q21 gains and are an independent adverse prognostic factor for the outcome of high-dose chemotherapy in patients with multiple myeloma

Abstract: Deletions involving chromosome 1p are frequent events in multiple myeloma (MM). As karyotyping and single nucleotide polymorphism-based mapping analysis identify a minimal common deletion region involving the 1p21 locus, we investigated the prevalence and prognostic significance of del(1p21) in 203 MM patients undergoing high-dose therapy and autologous SCT. 1p21 status was also evaluated in 16 patients with monoclonal gammopathy of undetermined significance (MGUS) and 41 patients with plasma cell leukemia (PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 20 publications
5
39
0
1
Order By: Relevance
“…15,38 In this study we referred only to "abnormal chr1", defined as del(1p) and/or gain (1q), which was present in 50.7% of patients: its poor prognostic impact on overall survival and progression-free survival was more significant than that of del(1p) or gain(1q) considered separately (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…15,38 In this study we referred only to "abnormal chr1", defined as del(1p) and/or gain (1q), which was present in 50.7% of patients: its poor prognostic impact on overall survival and progression-free survival was more significant than that of del(1p) or gain(1q) considered separately (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Gains of 1q21 (36%) are of special interest, since amplifications of the 1q and/or deletions of 1p arm have been described recently to be predictors of poor outcome in the context of high-dose chemotherapy. 12 In addition, Shaughnessy et al investigated the gene expression profile of 532 newly diagnosed patients with myeloma and identified a 70-gene subset as an independent predictor of outcome end-points in a multivariate analysis. 23 Interestingly, 30% of genes included in the 70-gene predic-…”
Section: Discussionmentioning
confidence: 99%
“…By clustering analysis of chromosomal abnormalities, we recently found that non-hyperdiploid MM can be separated into three subgroups: first, the translocation t (11;14), which juxtaposes the immunoglobulin heavy chain locus (IgH) to the oncogene cyclin D1; second, deletion of 13q14, which is frequently associated with translocation t (4;14) and involves the oncogenes MMSET and FGFR3; and third, gain of 1q21. 6 Previous studies have identified the presence of del(13q14), del(17p13), +1q21 as well as t(4;14) and t(14;16) detected by FISH as predictors of shorter overall survival, [7][8][9][10][11][12] while t(11;14) was associated with improved survival. 13,14 The aim of the current study was to correlate frequent recurrent chromosomal aberrations, determined by interphase FISH, with patients' outcome in 315 treated patients who received high-dose chemotherapy followed by autologous SCT in our center.…”
Section: Introductionmentioning
confidence: 99%
“…In both pPCL and sPCL, the prevalence of poor-risk chromosomal abnormalities, such as del(17p), 4,5,16,17,21 del(13q), [4][5][6]13,16,17,22,26,27 del(1p21), 16,17,21,28 ampl(1q21), 16,17,21,27,28 and MYC translocations or amplifications, 5,17,29,30 is markedly higher compared with newly diagnosed MM (Table 1). Coding mutations in TP53 are common in both pPCL and sPCL, 5,31 whereas these mutations are rare in newly diagnosed MM.…”
Section: Secondary (Epi)genetic Eventsmentioning
confidence: 99%